(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The preserit paper describes Upper Devonian conodont fauna from the black and bluish limestone succession lying immediately above the Muth Quartzite exposed near the village Tanze, Luneak valley, Ladakh.